1977
DOI: 10.1021/jm00216a015
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biochemical evaluation of nucleosides of naphthoquinone heterocycles

Abstract: The synthesis, characterization, and biochemical evaluation of 1-beta-D-ribofuranosylnaphtho[2,3-d]imidazole-4,9-dione (3), 2-beta-D-ribofuranosylnaphtho[2,3-d]pyrazole-4,9-dione (6), and 2-beta-D-ribofuranosylnaphthol[2,3-d]triazole-4,9-dione (9) are reported. These quinone nucleosides and the corresponding quinone heterocycles were tested as inhibitors of purine nucleotide biosynthesis in Ehrlich ascites cells. The nucleosides 3 and 9 and naphtho[2,3-d]imidazole-4,9-dione were effective inhibitors of hypoxan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1977
1977
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Evaluation of the cytotoxicity of these 1-substituted-2-methylnaphth [2,3-d]imidazole-4,9-dione derivatives (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) showed that the N-ethyl analog (5) displays strong cytotoxicity. Therefore, we prepared a series of 1-ethyl-2-substituted-naphth[2,3-d]imidazole-4,9-diones (22-28) where the N-1 substituent was fixed as chloride and 1 to react under these conditions has been previously reported by Hoover.…”
Section: Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of the cytotoxicity of these 1-substituted-2-methylnaphth [2,3-d]imidazole-4,9-dione derivatives (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) showed that the N-ethyl analog (5) displays strong cytotoxicity. Therefore, we prepared a series of 1-ethyl-2-substituted-naphth[2,3-d]imidazole-4,9-diones (22-28) where the N-1 substituent was fixed as chloride and 1 to react under these conditions has been previously reported by Hoover.…”
Section: Chemistrymentioning
confidence: 99%
“…The quinone moiety is involved in a wide variety of biochemical processes including electron transport and oxidative phosphorylation. Biological activities that have been reported for quinones and quinone derivatives include enzyme inhibition and antibacterial, antifungal, and anticancer activities. , Numerous structurally diverse quinone derivatives have been synthesized and investigated; one class of such compounds is the heterocyclic quinones, including imidazole derivatives of 1,4-naphthoquinones. , Naphth[2,3- d ]imidazole-4,9-dione and its 1-β- d -ribofuranosyl derivative were prepared in a study of naphthoquinone heterocycles and were found to be effective inhibitors of hypoxanthine phosphoribosyltransferase, which is involved in an initial step in purine nucleotide biosynthesis. In addition, the naphthoquinone psychorubrin was isolated as a cytotoxic natural product from Psychotria rubra ( Chiou Chie Mu ) (Rubiaceae) by this laboratory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Thus, among quinones, naphthoquinones have been found to possess good fungicidal 4,5 as well as antimalarial activities. 6 On the other hand, quinones fused to oxazole or thiazole nuclei have been endowed with good bactericidal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the importance of quinones which posses a wide spread application in various fields including use as fungicides [1][2][3], antibacterial [4][5][6], antimalarial [7] and as antitumoral [8], we decided to synthesize some new heterocyclic quinones starting with aryl-1,4-benzoquinones (1) [9] hoping that such compounds would have certain required biological effects or other industrial applications.…”
mentioning
confidence: 99%